The Weight of Masculinity: An Exploratory Analysis of Male Technical Workers in Karawang - Derri Agusta Putra; Akbar Rifqi Farisan (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The technical and engineering sectors have long been constructed as male-dominated environments that reinforce specific hegemonic masculinity norms. While these norms prioritize resilience and logic, they often create significant barriers to mental health help-seeking and emotional expression. This study aims to explore the construction of masculinity among technical employees and how these gendered expectations influence their mental well-being and coping strategies. Using a qualitative approach, Focus Group Discussions (FGDs) were conducted with three employee groups. Data were analyzed using inductive thematic analysis. Four major themes emerged: first, Physical and mental resilience as an ideal standard; second, the logic-emotion dichotomy and the